The Impact of Socialization on Collaborative Learning Method in E-Learning Management System (eLMS) - Aljasim Muhisn, Zahraa Abed; Ahmad, Mazida; Omar, Mazni; Muhisn, Sinan Adnan (International Journal of Emerging Technology in Learning, 2019)
The rapidly increasing use of information and communication technology (ICT) in the academic community allows learners to access information and academic content anywhere at anytime. e-Learning Management System (eLMS) is one of the popular tools that are increasingly being used in higher education institutions to support and manage teaching and learning. This empirical study was thus conducted to investigate the impact of e-learning on the socialisation among students in Iraq. The sample comprised of 109 undergraduate students from College of Information Technology at a public university in Iraq, all of whom were active eLMS users. The participants took part in a survey, the results of which indicated that knowledge can be effectively transferred from lecturer to students via eLMS, which motivates students to share knowledge with peers through socialisation process, which is one of the critical aspects of Knowledge Management (KM).